Програмна система для автоматизації управління персоналом - Посипайко, О. В. (ХНУРЕ, 2021)
The purpose of this work is to overview and analyze the process of the human resources management in any organization and show the infulence of effective sotware on employees and managers. The main aim of this article is to not only show some examples of using HRM systems but also, to define a problem that just a small amount of them can be used both managers and emploees. This work is supposed to find out the best way of writing reports and make all processes visible for all emploees so that it can be applied for big and small organizations.
Науковий керівник – к.т.н., доц. каф. ПІ Чуприна А.С.
Keywords: програмна система; автоматизація управління персоналом